Asiatic acid induces colon cancer cell growth inhibition and apoptosis through mitochondrial death cascade - Tang, Xue-Lian; Yang, Xin-Ying; Jung, Hyun-Ju; Kim, Sung-Yeon; Jung, Suk-Yul; Choi, Du-Young; Park, Won-Cheol; Park, Hyun (Biological & pharmaceutical bulletin, 2009)
Cancer is one of the leading causes of death in the world. The triterpenoid compound asiatic acid derived from the tropical medicinal plant Centella asiatica displays cytotoxic activity on fibroblast cells and several other kinds of cells. The present work studies asiatic acid-mediated growth inhibition of cancer cells and the underlying mechanism. Asiatic acid markedly inhibited cancer cell proliferation. Apoptosis of SW480 human colon cancer cells was induced by asiatic acid as shown by flow cytometry, DNA fragmentation and nuclear chromatin condensation experiments. Through increasing mitochondrial membrane permeability and cytochrome c release from mitochondria into cytosol, asiatic acid induced caspase-9 activity, which further activated caspase-3 and poly(ADP-ribose) polymerase cleavage resulting in irreversible apoptotic death in the tumor cells. Taken together, these results suggest that mitochondrial death apoptosis cascade plays very important roles in asiatic acid-induced cancer apoptosis.